Application of The Law to Children Who Do Not Have The Right to Possess or Carry Sharp Weapons - Elmansah Elmansah; Amiruddin Hanafi; Fidyah Faramita Utami (Rechtsvinding, 2026)
The aim of this research is to determine the application of the law for children who commit the crime of carrying sharp weapons without a valid permit. This research uses a normative juridical legal method. In this case, the application of the law to children is not appropriate when viewed from the violation of the law committed by the child, the child does not understand the consequences of an act that the child has committed, in this case the child is still detained even though the child can get diversion because this is not a repetition of the crime, and does not cause fatalities, if we look at Law Number 11 of 2012 concerning the Child Criminal Justice System, where diversion can be attempted in cases of children, however in this case the Public Prosecutor did not attempt diversion by considering the age of the child and several other reasons, as well as the judge's decision which if we look at the Law of the Republic of Indonesia Number 11 of 2012 concerning the Child Criminal Justice System, is contained in Article 7 paragraph (1) and paragraph (2), and Regulation of the Supreme Court of the Republic of Indonesia Number 4 of 2014 concerning Guidelines for Implementing Diversion in the Child Criminal Justice System, is contained in Article 3.